Comprehensive comparative study of Chiari-like malformation in veterinary and human medicine - Jung, J. H; Park, H; Kim, W. S; Yoon, H. Y (Veterinární medicína, 2024)
This review aims to enrich our understanding of Chiari-like malformation (CLM) by combining human and veterinary insights, and providing a detailed cross-species overview. CLM is a developmental abnormality characterised by caudal displacement of the hindbrain into the foramen magnum due to an entire brain parenchymal shift caused by insufficient skull volume. This malformation leads to a progressive obstruction at the craniocervical junction, which disrupts the normal cerebrospinal fluid flow, leading to secondary syringomyelia. The clinical signs of CLM and syringomyelia include phantom scratching, head tilt, head tremor, ataxia, tetraparesis, pain, muscle atrophy, and scoliosis or torticollis. Magnetic resonance imaging remains the gold standard for diagnosing CLM, since it allows the visualisation of abnormal findings such as the caudal cerebellar herniation, caudal cerebellar compression from occipital dysplasia, and attenuated cerebrospinal fluid cisternae. Although various medical and surgical interventions, including foramen magnum decompression, can provide temporary symptomatic/clinical sign relief, current literature shows a lack of sustained long-term efficacy. Therefore, additional research is needed to evaluate the long-term effects of existing treatment strategies and to compare different techniques utilised in conjunction with foramen magnum decompression.